2015
DOI: 10.1097/cad.0000000000000284
|View full text |Cite
|
Sign up to set email alerts
|

N-Farnesyloxy-norcantharimide inhibits progression of human leukemic Jurkat T cells through regulation of mitogen-activated protein kinase and interleukin-2 production

Abstract: This study investigated the anticancer effects of N-farnesyloxy-norcantharimide (NOC15), a newly synthesized norcantharidin (NCTD) analogue, on human leukemic Jurkat T cells and the signaling pathway underlying its effects. We found that the half maximal inhibitory concentration (IC50) of NOC15 on Jurkat T cells is 1.4 μmol/l, which is 11.14-fold (=15.6÷1.4) smaller than the 15.6 μmol/l of NCTD on Jurkat T cells, whereas the IC50 of NOC15 on human normal lymphoblast (HNL) is 207.9 μmol/l, which is 8.17-fold (=… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…It can not only enhance the inhibitory effect on cancer cells, but also reduce side effects [177,178]. In addition, some other NCTD derivatives and liposomes, such as NOC15 (N-farnesyloxy-norcantharimide) [179] and SG-NCTD-LIP (NCTD-loaded liposomes modified with stearyl glycyrrhetinate) [176], also can effectively improve the anticancer activity and reduce the toxicity of NCTD. However, although these studies have shown that NCTD analogues have a very broad application prospect, most of the existing NCTD analogues have no obvious selectivity for tumors and targets.…”
Section: Discussionmentioning
confidence: 99%
“…It can not only enhance the inhibitory effect on cancer cells, but also reduce side effects [177,178]. In addition, some other NCTD derivatives and liposomes, such as NOC15 (N-farnesyloxy-norcantharimide) [179] and SG-NCTD-LIP (NCTD-loaded liposomes modified with stearyl glycyrrhetinate) [176], also can effectively improve the anticancer activity and reduce the toxicity of NCTD. However, although these studies have shown that NCTD analogues have a very broad application prospect, most of the existing NCTD analogues have no obvious selectivity for tumors and targets.…”
Section: Discussionmentioning
confidence: 99%
“…Jurkat cells are an immortalized line of human T lymphocyte cells of highly spherical shape with the diameter ranging from 10 to 16 µm, first derived from the peripheral blood of a 14-year-old boy suffering from T cell leukemia [33]. Jurkat cells can be transfected and can produce interleukin-2 (IL-2) [34,35]. Therefore, they can be used as the host to study T-cell receptor (TCR) signaling which are greatly related to adoptive cell therapy-a novel treatment of several advanced forms of cancer and many other researches on cancer treatments [36].…”
Section: Introductionmentioning
confidence: 99%
“…The “net effect” has been devised to compare the net therapeutic effects of 2 anticancer drugs [ 19 ] so that the therapeutic effect of one anticancer drug relative to the other can be realized. Since the definition of “net effect” involves 2 drugs and 2 kinds of cell lines, it cannot be used to evaluate the therapeutic effect and toxicity of a single drug.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous study, the anticancer activity ratio of drug X over drug Y toward cancer cells and the toxicity ratio of drug X over drug Y toward normal cells were defined as [ 19 ] …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation